2008
DOI: 10.1002/chin.200827020
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Decomposition of Perovskite‐Type Hydrides, MMgH3 (M: Na, K, Rb).

Abstract: Magnesium I 1200Synthesis and Decomposition of Perovskite-Type Hydrides, MMgH3 (M: Na, K, Rb). -The title compounds are synthesized by ball milling using powders of NaH, KH, Rb, and MgH2 as starting materials followed by heat treatment (673 K, 1.0 MPa H2, 3 h). NaMgH3 decomposes in a two-step reaction, whereas KMgH3 decomposes in a single-step reaction. RbMgH3 seems to decompose in a two-step reaction. The phase stability of these perovskite-type hydrides changes in the order RbMgH 3 > KMgH 3 > NaMgH 3 . -(KOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…6,7,33,34 NaMgH 3 also can be produced directly by the ball milling of NaH + MgH 2 . 35 The NaMgH 2 F was reported as a product of the hydrogenation of a mixture of NaF + Mg 1:1 molar at 480 °C for 24 h under 10 bar of hydrogen pressure. 20 NaMgH 2 F is a byproduct of the hydrogenation of NaH−NaF−MgB 2 presented in this report.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,33,34 NaMgH 3 also can be produced directly by the ball milling of NaH + MgH 2 . 35 The NaMgH 2 F was reported as a product of the hydrogenation of a mixture of NaF + Mg 1:1 molar at 480 °C for 24 h under 10 bar of hydrogen pressure. 20 NaMgH 2 F is a byproduct of the hydrogenation of NaH−NaF−MgB 2 presented in this report.…”
Section: Discussionmentioning
confidence: 99%
“…28 A high temperature is required for releasing molecular hydrogen from light perovskitetype hydrides. 14 Komiya et al 29 synthesized NaMgH 3 , KMgH 3 , and RbMgH 3 hydrides via a ball-milling method and found that different hydrides have different decomposition pathways at temperatures ranging between 673 and 723 K. Doping suitable elements is strategic to help the dehydrogenation process for most hydrides, making hydrides unstable. 30−33 In comparison with NaMgH 3 , 34 Na 0.9 K 0.1 MgH 3 experimentally exhibited enhanced dehydrogenation performance owing to its reduced structural stability.…”
Section: ■ Introductionmentioning
confidence: 99%